Imunitas Negara Asing di Forum Pengadilan , Nasional dalam Kasus Pelanggaran HAM Berat: Studi kasus Putusan The European Court on Human Right dalam Al-Adsani vs The United Kingdom 21 Nopember 2001 - sefriani sefriani (Fakultas Hukum Universitas Islam Indonesia, 2004)
It is the time that the International Human Rights regulate civil accusation to the state of serious Human Rights offender and forum or the court applied by the State automatically. It will be lose theimmunity when he make these serious human rights offende. ln order that the litigant is not the winnerin formal, so international law instrument both bilateral and regional or universal must regulate the further state property immunity.